HUBUNGAN ANTARA INFORMASI ASIMETRI DAN PRAKTEK PERATAAN LABA DI INDONESIA - Wasilah, Wasilah (Jurnal Akuntansi dan Keuangan Indonesia, 2005)
This paper conducts an empirical investigation about the relationship between information asymmetry and earnings management in Indonesia. When information asymmetry is high, the stakeholders do not have any information or resources to monitor and to know manager’s activities which give rise to the practice of earnings management. To provide evidence practices of earning managements and information asymmetry, this paper uses aggregate accruals with modified Jones model and market microstructure theory. This paper employs return volatility, trading volume and quotes price for bid ask spread to proxy in market microstructure. This paper employs generalized least squares with 60 firm balanced panel data in the 1994-199, and also addresses about the effect of Indonesian financial crisis to the relationship between information asymmetry and earnings management. We compare sub-sample before and in the financial crisis period. Empirical result suggests a positive relationship between information asymmetry as measured by bid ask spreads and the level of earnings management in Indonesia. This positive relationship is not affected by Indonesian financial crisis.